Development of an e-Diary Service for Deployment on the UFH network (International Journal of Engineering and Computer Science, 2017)
Diaries play a critical role in the management of work schedules in societies and working environments. The result of their use is proper decision-making and time-management. This research project focused on the development of an e-Diary Service system for employees and students at the University of Fort Hare (UFH). This university is situated in a town called Alice in the Eastern Cape province of South Africa. The development of the e-diary was aimed at addressing the problems encountered in the use of hard copy diaries for the management of work schedules at UFH. It has always been a problem using a hard-copy diary for managing work schedules because of the irregularities and inconsistencies associated with its use. These include among others the misplacement or loss of recorded information and failure to meet set targets and attend to some important scheduled events due to lack of a reminder-alert in a hard copy diary. The system was thus developed to provide a suitable solution to these irregularities and help its users to manage their work schedules in an easy, fast, safe and cost-effective manner. Its functions include among many others the ability to allow users to record, update, view and delete their work schedules while also facilitating for the important functionality of sending reminders to users with regards to their work schedules via electronic mail or Short Message Service (SMS).